No Strings Attached: The Impact of an Unconditional Prenatal Income Supplement on First Nations Birth and Early Childhood Outcomes - Brownell, Marni; Chartier, Mariette; Nickel, Nathan; Campbell, Rhonda; Enns, Jennifer; Phillips-Beck, Wanda; Chateau, Dan; Burland, Elaine; Sarkar, Joykrishna; Lee, Janelle Boram (International Journal of Population Data Science, 2018)
Introduction In Manitoba, low-income pregnant women are eligible for the Healthy Baby Prenatal Benefit (HBPB), an unconditional income supplement provided during the second and third trimester of pregnancy. HBPB is associated with improved birth outcomes for Manitoba women; its association with birth outcomes for First Nations (Indigenous) women is unknown. Objectives and Approach To determine the association between HBPB and First Nations’ (FN) newborn and early childhood outcomes, we linked whole-population data from health, public health, family services and education. We included only FN women receiving income assistance during pregnancy (n=7074) to develop comparable treatment (received HBPB; n=5283) and comparison (no HBPB; n=1791) groups. Propensity score weighting adjusted for differences in maternal characteristics between groups. Multi-variable regressions compared groups on breastfeeding initiation, low birth weight, preterm birth, small- and large-for-gestational age, Apgar scores, complete immunizations at 1 and 2 years, and developmental vulnerability in kindergarten measured with the Early Development Instrument (EDI). Results Receipt of the HBPB was associated with reductions in low birth weight births (adjusted Relative Risk (aRR): 0.77; 95% CI: 0.63, 0.93) and preterm births (aRR: 0.78 (0.68, 0.90)), and increases in breastfeeding initiation (aRR: 1.05 (1.00, 1.09)) and large-for-gestational age births (aRR: 1.11 (1.01, 1.23)). HBPB receipt during pregnancy was also associated with increases in 1- and 2-year immunizations for FN children (aRR: 1.14 (1.09, 1.19), and aRR: 1.28 (1.19, 1.36), respectively). Reductions in the risk of being developmentally vulnerable in the language and cognitive domain of the EDI were also found for FN children whose mothers had received the HBPB during pregnancy (aRR: 0.85 (0.74, 0.97). Conclusion/Implications A modest unconditional income supplement during pregnancy was associated with improved birth outcomes, increased immunization rates, and improved language and cognitive development at kindergarten for children born to low-income First Nations women. Long-term strategies to address structural inequities and the ongoing effects of colonization are also needed.